Uniform fiber-like polymeric micelles of controlled length containing a photo-cleavable core: Versatile templates toward functional nanotubes. (15th June 2021) - Ruan, Junyi; Xiao, Yan; Ma, Junyu; Huang, Xiaoyu; Lu, Guolin; Feng, Chun
Graphical abstract: We report a versatile route to prepare functional inorganic nanotubes by using uniform fiber-like micelles of controlled length containing a photo-cleavable core as templates. Highlights: Uniform nanofibers containing a crystalline π-conjugated OPV, a P2VP corona and a photo-cleavable junction were generated by living CDSA. The resulting nanofibers can serve as a versatile template to fabricate inorganic nanotubes of controlled length. Pt(0)-embedded silica nanotubes exhibited much higher catalytic activity as a consequence of the presence of porous channel. Abstract: Inorganic nanotubes with unique and well-defined porous structures show promising applications in diverse functional materials. However, it remains a challenge to fabricate inorganic nanotubes with precise length controllability. Herein, we report the synthesis of block copolymers consisting of a crystalline π-conjugated oligo( p -phenylenevinylene) (OPV) block, a hydrophilic poly(2-vinylpyridine) (P2VP) segment and a photo-cleavable o -nitrobenzyl (ONB) junction. By taking advantage of crystallinity of OPV segment, self-seeding approach of living crystallization-driven self-assembly was employed to generate uniform fiber-like micelles composed of an OPV core and a P2VP corona. The P2VP corona was then used to host the formation of silica, titania and Pt(0)-embedded silica shell. After the photo-cleavable OBN junctions were broken under light irradiation, the OPV core can be removed in a good solvent for OPV segments to give silica, titania and Pt(0)-embedded silica nanotubes. Significantly, the Pt(0)-embedded silica nanotubes exhibited much higher catalytic activity toward the reduction of p -nitroaniline than Pt(0)-embedded silica nanofibers with the same Pt content, probably owing to the presence of porous channel for nanotubes. This work opens a new avenue to fabricate inorganic nanotubes of controlled length.